Functionalized periodic mesoporous organosilicas: from metal free catalysis to sensing. Issue 23 (29th May 2019) - Bourda, Laurens; Jena, Himanshu Sekhar; Van Deun, Rik; Kaczmarek, Anna M.; Van Der Voort, Pascal
Abstract : A functionalized PMO was used as a metal-free catalyst in CO2 fixation and, after grafting with Ln 3+ ions, in various luminescence applications. Abstract : In this work a widely usable post-modification route for periodic mesoporous organosilicas (PMOs) was developed. Using the developed method, two diverse ligands, picolinic acid (Pic) and 4, 4′, 4′′, 4′′′-porphyrin-5, 10, 15, 20-tetrayltetrabenzoic acid (Porph), were successfully covalently coupled onto the PMO material and well-characterized. Both obtained materials show high BET surface areas (565 m 2 g −1 forPic@PMO, 483 m 2 g −1 forPorph@PMO and 548 m 2 g −1 for the unmodified PMO) and pore sizes (5.1 nm). The materials were subsequently tested for their catalytic activity in the cycloaddition of epoxide and CO2, a frequently studied carbon capture and utilization reaction. Interestingly, both materials showed very good reactivity (with conversions of up to 90%) as metal free heterogeneous catalysts and proved to be perfectly stable in recyclability and aging tests. Moreover, by (co-)grafting Eu 3+ and Tb 3+ ions ontoPic@PMO and Yb 3+ ions ontoPorph@PMO a strong emission was observed in the visible and near-infrared (NIR) range, respectively.Eu, Tb@Pic@PMO showed potential for use as a temperature sensor in the physiological range (a maximum S r value of 2.11 %K −1 was obtained at 273 K), whileYb@Porph@PMO could efficiently be excited within the human tissue penetrating window showing characteristic Yb 3+ luminescence (with decay times of around 10 μs). These findings prove that simple modifications of this PMO can provide smart materials for very diverse applications.